Role Conflict among Members of the Civil Service Police Unit of South Sulawesi Province, Makassar City - Athira Sapira (Pustaka Digital Indonesia, 2024)
This research is a type of qualitative research with the aim of finding out the role conflicts experienced by members of the Civil Service Police Unit of South Sulawesi Province, Makassar City. The type of data used is descriptive qualitative with data collection through observation and interviews. The research results that can be written show that members of the South Sulawesi Province Civil Service Police Unit experience moderate role conflict when carrying out their duties in the field. Looking at the dimensions of role conflict, researchers found that there are six factors that influence it, namely ignoring rules (undisciplined behavior), job transfer, difficulty making decisions, feelings of emotion, guilt and nonconformity role. From sixth The factor that most influences role conflict among members of the Civil Service Police Unit of South Sulawesi Province is ignoring the rules (undisciplined behavior). Even though they face role conflicts, they still uphold the humanist system, serve firmly and uphold preventive matters.